Major Bleeding in Patients With Coronary or Peripheral Artery Disease Treated With Rivaroxaban Plus Aspirin - Eikelboom, John W; Bosch, Jacqueline J; Connolly, Stuart J; Shestakovska, Olga; Dagenais, Gilles R; Hart, Robert G; Leong, Darryl P; O'Donnell, Martin; Fox, Keith A A; Bhatt, Deepak L; Cairns, John A; Tasto, Christoph; et al. (Journal of the American College of Cardiology, 2019)
In patients with coronary or peripheral artery disease, the combination of rivaroxaban 2.5 mg twice daily and aspirin 100 mg once daily compared with aspirin 100 mg once daily reduced major adverse cardiovascular events and mortality and increased bleeding. This study sought to explore the effects of the combination of rivaroxaban and aspirin compared with aspirin on sites, timing, severity, and management of bleeding in the COMPASS (Cardiovascular Outcomes for People Using Anticoagulation Strategies) study. This study reports, by treatment group, the number and proportion of patients; hazard rate ratios for bleeding according to site and severity; the timing of bleeding using landmark analyses; and the number and proportion of patients who received blood products and other hemostatic treatments. Of 27,395 patients enrolled (mean age 68 years, 22% women), 18,278 were randomized to the combination of rivaroxaban and aspirin or to aspirin alone and followed for a mean of 23 months. Compared with aspirin alone, the combination increased modified International Society on Thrombosis and Hemostasis major bleeding (288 of 9,152 [3.1%] vs. 170 of 9,126 [1.9%]), (HR: 1.70; 95% CI: 1.40 to 2.05; p < 0.001), International Society on Thrombosis and Hemostasis major bleeding (206 of 9,152 [2.3%] vs. 116 of 9,126 [1.3%]), (HR: 1.78; 95% CI: 1.41 to 2.23; p < 0.0001), and minor bleeding (838 of 9,152 [9.2%] vs. 503 of 9,126 [5.5%]), (HR: 1.70; 95% CI 1.52 to 1.90; p < 0.0001); the combination also increased the need for any red cell transfusion (87 of 9,152 [1.0%] vs. 44 of 9,126 [0.5%]), (HR: 1.97; 95% CI 1.37 to 2.83, p = 0.0002). The gastrointestinal (GI) tract was the most common site of increased major bleeding (140 of 9,152 [1.5%] vs. 65 of 9,126 [0.7%]), (HR: 2.15; 95% CI: 1.60 to 2.89; p < 0.001), and the increase in bleeding was predominantly in the first year after randomization. Approximately one-third of major GI bleeding was gastric or duodenal, one-third was colonic or rectal, and one-third was from an unknown GI site. The study investigators reported that approximately three-quarters of major bleeding episodes were of mild or moderate intensity. A similar proportion of patients in each treatment group who experienced major bleeding received platelets, clotting factors, or other hemostatic agents. The combination of rivaroxaban and aspirin compared with aspirin alone increased major bleeding, mainly from the GI tract. Most excess bleeding occurred during the first year after randomization, was of mild or moderate intensity, and was managed with conventional supportive therapy. (Rivaroxaban for the Prevention of Major Cardiovascular Events in Coronary or Peripheral Artery Disease [COMPASS]; NCT01776424).